Chitosan‐sodium lauryl ether sulfate particles and their use for adsorption of Cu(II) ions. Issue 7 (29th October 2013) - Peretz, Sandu; Florea‐Spiroiu, Manuela; Anghel, Dan F.; Munteanu, Cornel; Angelescu, Daniel; Stoian, Cristina; Zgherea, Gheorghe
Abstract The synthesis of small particles through the interaction between chitosan (CS) and sodium lauryl ether sulfate (SLES) was studied. Depending on working condition, microparticles at atmospheric pressure and ultrafine particles at high pressure have been obtained. At atmospheric pressure, the microparticles were formed instantaneously when the CS solution was dripped into the SLES aqueous solution. To obtain ultrafine particles, the surfactant solution in contact with high pressure carbon dioxide was sprayed into chitosan solution. Fourier Transform Infrared Spectroscopy proves the interaction between the sulfate groups of SLES and the amino groups of CS. The Scanning Electron Microscopy reveals that the microparticles are quasi‐spherical, but some of them can take the form of pellets depending on preparation conditions. The obtained microparticles were successfully used to uptake Cu(II) ions from aqueous solutions. The adsorption of Cu(II) depends on pH being maximum at pH = 5.5. The kinetic experiments demonstrated that Cu(II) adsorption onto CS/SLES microparticles obeys the Langmuir model. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40059.